A model of fatigue crack propagation in metals - Yakovleva, T.Yu.; Matokhnyuk, L.E. (Проблемы прочности, 2009)
A model of the formation and evolution of a local plastic deformation zone at the crack tip is proposed based on the analysis of the main physical processes taking place in a metallic material under the action of cyclic loads. An equation offatigue crack growth rate curves, which explicitly accountsfor the loadingfrequency, was derived. The equation applies to the whole range ofcrack lengths from short cracks to macroscopic ones.